Shenzao jiannao oral liquid, an herbal formula, ameliorates cognitive impairments by rescuing neuronal death and triggering endogenous neurogenesis in AD-like mice induced by a combination of Aβ42 and scopolamine. (15th September 2020) - Xiao, Honghe; Li, Hongyan; Song, Huipeng; Kong, Liang; Yan, Xin; Li, Yan; Deng, Yan; Tai, He; Wu, Yutong; Ni, Yingnan; Li, Wanyi; Chen, Jicong; et al.
Abstract: Ethnopharmacological relevance: According to the theory of traditional Chinese medicine (TCM), Alzheimer's disease (AD) is identified as "forgetfulness" or "dementia", and is mainly caused by "kidney essence deficiency" which ultimately induces "encephala reduction". Therefore, herbal formulas possessing the efficacy of nourishing kidney essence or replenishing brain marrow are commonly served as effective strategies for AD treatment. Shenzao jiannao oral liquid (SZJN), a traditional Chinese preparation approved by the China Food and Drug Administration (CFDA), is used for the treatment of insomnia and mind fatigue at present for its efficacy of nourishing kidneys. In present study, we found that SZJN could improve cognitive function of AD-like mice. Aims of study: This study aims to investigate the effects of SJZN on ameliorating cognitive deficits of AD-like mouse model, and to illuminate the underlying mechanisms from the perspective of neuroprotection and neurogenesis. Materials and methods: Kunming mice (28 ± 2 g) were randomly allocated into seven groups: control, sham, model, donepezil and SZJN groups (low, middle and high). The AD mouse model was established by A β 42 combined with scopolamine. SZJN were intragastrically administrated at doses of 0.3, 1.5 and 7.5 g/kg for 28 days. Morris water maze (MWM) test was applied to determine the cognitive function. Hematoxylin eosin (HE) and Nissl staining were carried out to evaluate pathological damages in the cortex and hippocampal tissues. To explore the protective effects of SZJN on multiple pathogenic factors of AD, protein levels of A β 42, glial fibrillary acidic protein (GFAP), Bax, Bcl-2, Caspase-3, synaptophysin (SYP), brain-derived neurotrophic factor (BDNF), and neurogenesis related proteins were assessed using Immunofluorescence (IF) and western blot analysis. In vitro, the AD cell model was established by transduction of APP695swe genes into Neural stem cells (NSCs) isolated from the hippocampal tissues of neonatal C57BL/6 mice. Cell viability assay and neurosphere formation assay were carried out to verify the efficacy of SZJN on proliferation of NSCs. Results: Our results demonstrated that SZJN (1.5 g/kg and 7.5 g/kg) treatment significantly ameliorated cognitive deficits of AD-like mice. SZJN (7.5 g/kg) treatment significantly retarded the pathological damages including neuronal degeneration, neuronal apoptosis, Aβ peptides aggregation and reaction of astrocytes in AD-like mice. In addition, SZJN (7.5 g/kg) increased the expression of BDNF and SYP, and restored the abnormal level of MDA and SOD in the brain of AD-like mice. Furthermore, SZJN treatment for 28 days remarkably increased the proliferation of NSCs evidenced by more Nestin + and BrdU + cells in the hippocampal DG regions, and increased the amount of mature neurons marked by NeuN both in the cortex and hippocampal DG regions. In vitro, SZJN treatement (16, 32, 64 mg/ml) promoted the proliferation of NSCs evidenced by the increased amount and enlarged size of the neurospheres (p < 0.05). Conclusions: Our findings indicated that SZJN could ameliorate cognitive deficits by protecting neurons from death and triggering endogenous neurogenesis. Therefore, SZJN may be considered as a promising agent to restore neuronal loss and deter the deterioration in AD patients. Graphical abstract: Shenzao jiannao oral liquid, an herbal formula, ameliorates cognitive impairments by rescuing neuronal death and triggering endogenous neurogenesis in AD-like mice induced by a combination of A β 42 and scopolamine. Image 1